Growth modulation in genu valgum secondary to multiple hereditary exostosis - Tharmaseelan, Shival; Kamisan, Norazian; Ismail, Imma Isniza (Lycia Press, 2024)
Hereditary Multiple Exostoses (HME) is a rare disease with a prevalence of 1:50,000, which can manifest in various ways. This cartilaginous tumor can appear in a spectrum, ranging from mobility restriction to chronic pain and alignment disorders. Literature often describes forearm deformities such as excessive radial bowing, ulnar shortening, and radial head dislocation. Factors resulting in genu valgus and specific treatment strategies are not frequently studied. Considerations specific to the disease, such as the morphology of the lesion, time taken for deformity correction, and timing of exostosis excision, should be taken into account when treating genu valgum in patients with MHE.